Magic Clips for Fixed Retention - Prakash, Amit; Chamania, Satish; Kambalyal, Prabhuraj B. (Orthodontic Journal of Nepal, 2015)
Despite major advances in orthodontic tooth movement, orthodontic retention remains a major problem. It has been estimated that only 10% of the population who have received orthodontics are still in acceptable occlusion as judged by orthodontists 20 years after retention. One of the means of maintaining stability has been the use of fixed retainers. This article will describe a very simple and effective method of stabilizing the retainer during bonding using clip. The method of stabilizing the fixed retainer described in this article is the most simplest, economical, least time consuming and also very effective method.